Multivariate statistical evaluation of heavy metals in the urine of opium individuals in comparison with healthy people in Western Iran - Azadi, Nammamali; Nakhaee, Samaneh; Farnia, Vahid; Pirsaheb, Meghdad; Mansouri, Borhan; Ahmadi-Jouybari, Toraj; Khanegi, Maryam (Environmental science and pollution research international, 2022)
The current study aimed to evaluate the levels of some toxic and essential elements (Pb, Cd, Cu, Ti, Ni, Cr, Co, Fe, Ca, Hg, Mn, Se, and Zn) in the urine of opium-addicted compared to non-addicted cases. In this study, 126 participants were recruited and their fasting urine samples were collected (63 opium-addicted and 63 non-addicted subjects served as the reference group). ICP-MS was utilized to detect the concentration of trace elements. Results exhibited that the concentration of all elements than Ni, Cu, and Zn was markedly different between the addicted and non-addicted groups. Compared to controls, the Cd, Cr, Co, Hg, Mn, Pb, Se, and Ti levels were higher among opium-addicted cases ( p < 0.05) whereas the Fe and Ca concentrations were higher among controls ( p < 0.05). Robust regression analysis showed no statistically significant effect of gender on element levels. It revealed that age was associated with the levels of Ni and Cu only and also the route of administration was related to the urinary levels of Co, Cr, Hg, and Mn. In conclusion, results confirmed that it is opium consumption that affects the concentration levels of most elements.